Critical Analysis of the Application of PSAK 105 in Mudharabah Financing at BMT Barokah Tegalrejo - Arifah; Qurotul Aini; Yeny Fitriyani (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
The suboptimal implementation of PSAK 105 on Mudharabah accounting within Islamic microfinance institutions forms the foundation of this study. Focusing on BMT Barokah Tegalrejo, the research critically examines the application of PSAK 105 across the dimensions of recognition, measurement, presentation, and disclosure. A qualitative descriptive-critical methodology was employed, with data primarily sourced from an in-depth interview with the institution’s manager. The fieldwork was conducted between December 4, 2024, and January 6, 2025. The findings reveal partial compliance with PSAK 105. Key areas of conformity include the initial recognition of investment, the application of cash-based measurement, income recognition based on financial projections, and the use of profit-sharing mechanisms. Nevertheless, notable deviations were observed in the accounting treatment of receivables after contract termination, the premature recognition of loss provisions prior to contract maturity, and deficiencies in financial statement disclosures. These inconsistencies potentially undermine the reliability and transparency of financial reporting. The study underscores the need for strengthened managerial comprehension of PSAK 105 and recommends the development of comprehensive standard operating procedures (SOPs) to support consistent and compliant financial reporting practices in Islamic microfinance settings. Keywords: PSAK 105, Mudharabah, Sharia Accounting, BMT, Financial Report